From Games to Structures. In the traces of Zoltan Dienes’ ideas - Bálint, Ágnes (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Zoltan Dienes the Hungarian origin mathematician and psychologist aimed at the renewal of mathematics teaching. He argued that teachers should promote the development of authentic mathematical thinking instead of teaching mathematical knowledge. The aim of teaching mathematics is the mental development of mathematical structures. For this purpose Dienes introduced games for children to gain mathematically relevant experiences. Through the accumulation of these experiences, argued Dienes, learners get to understand and represent the abstract mathematical structures. In the course of structure creation he emphasized the role of multiple embodiment of the abstract relations. In my paper I follow Dienes in analyzing the process how the structures develop as well as reveal the further psychological highlights in the background that Dienes failed to refl ect on. I think that the comprehension of mental structure creation leads us to better understanding of insight.